Iowa RBA, December 4, 1995 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1995)
Iowa RBA update for December 4, 1995. Highlights of the update include sightings of Evening Grosbeaks, Black-billed Magpie, White-winged Crossbill, Black-legged Kittiwawke, Glaucous Gull, Common Redpoll and an Iceland Gull. Also included are handwritten notes for the next week's update with sightings of a Long-eared Owl. Epson - sheet feed/flatbed